The Application of Article 87 of Law Number 30 of 2014 on Government Administration in State Administrative Court Decisions Related to Medical Disputes - Adji, Arga Setyo; Michelle Vincentia, Vania; Maulana Satrioaji, Abdillah; Dwi Purwanto, Andi; Haksama, Setya (PT ARRUS Intelektual Indonesia, 2025)
Medical disputes often arise from disagreements in healthcare services involving medical personnel, such as doctors and nurses, which may lead to patient injuries or death. Article 87 of Law No. 30 of 2014 provides a legal basis for courts to annul administrative decisions that are legally flawed or involve abuse of authority, thereby protecting medical personnel from unfair sanctions. This study employs a normative method with a statutory approach and finds that: 1) Article 87 offers significant legal protection for medical personnel; 2) This article promotes transparency and accountability in administrative decisions within the healthcare sector; 3) The implementation of Article 87 also safeguards patients' rights by ensuring decisions are examined fairly and transparently; 4) The application of Article 87 principles contributes to improving the quality of healthcare services by encouraging objective and professional administrative decisions.